Research and Development the Prescription of Sofosbuvir Tablets (Communications in Computational Chemistry, 2018)
The prescription of sofosbuvir tablets was screened to select the bestprescription proportions. Methods: According to the prescription technology of foreignlisted tablets “sovaldi®”, experiments of diluents, disintegrating agents, binders,lubricants and coating process were investigated, including the stability study ofself-made samples and reference tablets under the conditions of high temperature, highhumidity and illumination. We aimed to screen a reasonable prescription process.Results: Prescription process was ultimately determined including: sofosbuvir 400 mg,mannitol 360 mg, microcrystalline cellulose 360 mg, cross-linked sodiumcarboxymethyl cellulose 60 mg, magnesium stearate 14 mg, gum arabic 6 mg, opadryfilm coating powder 36 mg, and chose purified water as a binder. Conclusion: Thedetermined prescription process was stable, and the production process was not harsh,it was suitable for scale-up production. The results of stability study and the dissolutionbehavior in vitro were similar to those of commercial products, so the prescription isdesign reasonably.
Keywords: sofosbuvir tablets; stability study; prescription technology; reference tablet “sovaldi$^® $”.